The participation of a lawyer in civil proceedings: current issues (Journal of actual problems of jurisprudence, 2018)
This article discusses the role, value and actual problems of the participation of a lawyer in civil proceedings. The author proposed specific measures aimed at enhancing its role and values.Key words: the lawyer, advocacy, legal representation, the representative of the Commission.